Evaluation of Cytotoxicity, Cell Cycle, and Apoptosis Induction of Methyl Thiosemicarbazone Complex with Copper on K562 Cell Line - Neda Kazemi Motlagh; Saeed Hesami Tackallou; Majid Mahdavi; Mahdi Hosseinzadeh (Journal of Research in Applied and Basic Medical Sciences, 2022)
Background & Aims:  Chronic human myeloid leukemia (CML) is caused by mutations and changes in stem cells. This study aimed to investigate the toxicity, apoptosis, and cell cycle of thiosemicarbazone complex with copper on the human chronic myelogenous K562 leukemia cell line. Materials & Methods:  After culturing the human K562 cell line, it was exposed to the combination of methyl thiosemicarbazone complex with copper in different concentrations and durations. Trypan blue dye exclusion test and MTT were used to determine cell viability and cell growth inhibition. The occurrence of apoptosis was examined by dual acridine orange/ethidium bromide (AO/EB) fluorescent staining and fluorescence microscopy, cell cycle analysis, and dual PI/AnnexinV staining using flow cytometry. Results:  The data obtained from the present study showed morphological changes resulting from apoptosis and cell cycle arrest in Sub G1 in the presence of phosphatidylserine in the outer leaflet of the cell membrane due to treatment with thiosemicarbazone compound. It also decreased the biological growth of the K562 cell line in a concentration-/ and time-dependent manner. Conclusion:  effective at low concentrations and short duration of action, this compound can be a suitable candidate for future pharmacological studies on treating CML.